Identification and evolutionary analysis of NAC transcription factors in Eriobotrya japonica: implications for sugar-acid regulatory networks during fruit development - Zhang, Huiling; Yang, Meng; Ye, Chengyang; Chen, Minghui; Gu, Hailing; Fan, Xiurun; Yang, Chencong; Chen, Junwei; Xu, Kai; Wu, Boping (Frontiers in Plant Science, 2025)
Loquat (Eriobotrya japonica) is an important subtropical evergreen fruit tree of the Rosaceae family that possesses significant edible and economic value. The NAC transcription factor family, as plant-specific regulatory factors, not only participated in plant growth and development but also played crucial roles in fruit quality formation. Through genome-wide analysis, this study identified 117 NAC family members in loquat, which were phylogenetically classified into 14 distinct subfamilies. Chromosomal localization revealed that 114 genes were unevenly distributed across 17 chromosomes, while the remaining 3 were located in genomic scaffold regions. Collinearity analysis indicated that loquat NAC genes primarily underwent purifying selection and showed high homology with NAC genes from other Rosaceae species. Cis-acting element prediction analysis suggested these genes were extensively involved in various biological processes, including abiotic stress responses, hormone signal transduction, and growth regulation. Expression pattern analysis based on transcriptome data further uncovered differential expression characteristics of NAC genes across different loquat cultivars and fruit developmental stages. Notably, correlation analysis identified several NAC candidate genes that were significantly associated with fruit sugar-acid content. This study provided the first comprehensive and systematic characterization of the NAC gene family in loquat, establishing an important foundation for elucidating the molecular mechanisms by which NAC transcription factors regulate loquat fruit flavor quality.